Microscopic studies on modified wall structure and lignin topochemistry in xylem fibres of poplar after wounding - Frankenstein, Claus; Schmitt, Uwe (Maderas. Ciencia y Tecnología, 2025)
Information about fine structure following wounding in differentiating xylem tissue is still scarce. This study provides information on cell wall modifications with special emphasis on lignin distribution in xylem fibres of poplar differentiating at the time of wounding. Samples were collected from wounded Populus spp. trees after response periods of up to twenty-three months and processed for microscopic analyses. General studies on the wall structure of wound-adjacent xylem fibres were carried out with light and transmission electron microscopy, whereas lignin distribution patterns of these cells were examined by UV-microspectrophotometry. Xylem fibres close to the wound and within a transition zone between differentiated xylem laid down prior to and tissue laid down after wounding developed a distinctively thicker secondary wall than normal fibres. These modified walls also showed a slightly higher lignin content, than normal and a heterogeneous lignin distribution in the middle lamella and the secondary wall. Wounding in poplar induces a modified wall structure and lignin topochemistry in xylem fibres differentiating at the time of wounding. It is assumed that this wound response is part of the compartmentalization process and therefore contributes to an increased resistance.